Analisis Pengujian Usability untuk Membandingkan Kemudahan Transaksi pada BukaLapak dengan Lazada - Tegar Wahyudi; Fitri A. Bachtiar; Mochammad Chandra Saputra (Fakultas Ilmu Komputer (FILKOM), Universitas Brawijaya, 2018)
Lazada and BukaLapak are e-commerce that have been applying mobile application technology. Lazada and BukaLapak have reting and highest downloader compared to its competitors. But earlier in the year 2017 Lazada has received many complaints in reference to problems of Usability. This research use theory of McCall in which Usability has 3 matrix, namely: Operability, Communicativeness and Training. Operability matrix is to see the extent to which users can operate an application, Communicativeness matrix is to see the suitability of data input with output data seen from the users. Training matrix is to see the extent to which new users can operte application. The research began with the making of instruments, data collection, and continued with the statistical testing. In the making of the instruments the questions are based on the article belong to McCall. Data collection questionnaire used to measure Operability and Communicativeness, whereas the task used to measure Training. Statistical test using independent t test to see a comparison between the Lazada and BukaLapak. From the results of the comparison of the three matrix such that for Operability, Communicativeness and Training there is no difference between BukaLapak and Lazada.